Trusting the institutions in Malaysia: an Islamic sociological perspective - Altabaa, Homam; Idid, Syed Arabi (2019)
This study seeks to examine the expressions of trust from an Islamic sociological perspective towards numerous social, public and governmental institutions in Malaysia. Trust essentially revolves around the dependability of persons, objects and systems. It is an important and foundational value in the Islamic worldview and ethical environment. Needless to say, trust is implicit as a basis for any interactions or arrangements between members of a given community whether these members engage in social, economic or political activities. The factors that affect the levels of trust within a society towards its various institutions are numerous, ranging from the political and macroeconomic to the personal and subjective. In April of 2019, a survey was conducted across Malaysia that asked hundreds of Malay/Muslim respondents about their levels of trust in local institutions. These covered both social, public and governmental institutions, i.e., parents, siblings, relatives, spiritual/religious leaders, community leaders, friends, neighbours, teachers, the military, the civil service, the legal and judiciary system, the police, local big companies, mass media, the parliament, the federal government, political leaders, and political parties. Before delving into the implications of this survey from the Islamic sociological perspective, the paper first explores the religious and sociological dimensions of the concept of trust in Islam. In brief, the moral imperative placed on trust by Islam towards all its followers individually or in various social hierarchies is definitive and unavoidable. The survey determines whether or not the levels of trust among Malaysian Muslims reflect the Islamic ideals of a Muslim community. The implications of these levels for development from an Islamic sociological perspective are investigated and analysed as the major contribution of this study.